Against the cold war - Sen, Chanakya (Bombay, 1962)
When this book was in the final stage of printing, an event of magnitude took place on the soil of India. On December 18, 1961, Indian troops moved into the three Portuguese enclaves of Goa, Daman and Diu and liberated them in 24 hours. The Portuguese soldiers surrendered without resistance.
Keywords: World History-1939-1945